Computer Simulation and Optimization of Transport Distances of Order Picking Processes. (2017) - Bučková, Monika; Krajčovič, Martin; Edl, Milan
Abstract: This article deals with optimizing of transport distances in orders picking processes. Article shows solution how to optimize orders picking in warehouse using dynamic simulation. In article basic steps of order picking planning process are described in order to minimize distances traveled by truck or human. The basis of this solution is execution of computer simulation and simulation experiments for faster finding of correct solution, which causes company cost reduction.